Understanding the Potential for Collaborative Search Technologies in Clinical Settings - Morris, Meredith Ringel; Morris, Dan (CIR '11 Proceedings of the 3rd international workshop on Collaborative information retrieval, 2011)
In this position paper, we report the findings of interviews with four medical doctors regarding the use of internet search by doctors and patients in support of the treatment process; we particularly focus on opportunities for collaboration between doctors and patients in clinical information retrieval scenarios.